Talking about (my) Generation': Creativity, Practice, Technology & Talk - Martin, David; O'Neill, Jacki; Randall, Dave (Springer, 2009)
This paper describes the findings of an ethnomethodological enquiry into the work of graphic designers. We explore the collaborative nature of graphic design as undertaken by a small team of designers working in a packaging design company. In doing so, we attempt to explicate the way in which practice, talk and technology are intricately bound up in such a way as to constitute a creative process. We describe a series of scenic features, ‘orderings’, and ‘talkaboutables’ which are characteristic of this process and which may be entailed in other creative contexts and hence can be important topics for CSCW design for creativity